2008
DOI: 10.1161/hypertensionaha.108.119602
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Vitamin D Receptor Is Increased in the Hypertrophic Heart

Abstract: Abstract-The liganded vitamin D receptor (VDR) is thought to play an important role in controlling cardiac function.Specifically, this system has been implicated as playing an antihypertrophic role in the heart. Despite this, studies of VDR in the heart have been limited in number and scope. In the present study, we used a combination of real-time polymerase chain reaction, Western blot analysis, immunofluorescence, and transient transfection analysis to document the presence of functional VDR in both the myoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
122
0
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(132 citation statements)
references
References 35 publications
3
122
0
7
Order By: Relevance
“…Of note, cardiomyocytes in rats express CYP27B1 and respond to cholecalciferol in vitro. 60 Studies from our group and other have already shown that cholecalciferol supplementation is a safe way to increase 25 (OH)D concentrations in kidney transplant recipients, but the small number of treated patients included in these studies and their short follow-up do not allow any conclusion on the effect of these treatments on kidney function. [61][62][63] Our results should encourage randomized controlled trials evaluating the effect of early cholecalciferol supplementation on renal allograft function and provide valuable information on the magnitude of the expected effects of such treatments on renal function and histologic features.…”
Section: Discussionmentioning
confidence: 94%
“…Of note, cardiomyocytes in rats express CYP27B1 and respond to cholecalciferol in vitro. 60 Studies from our group and other have already shown that cholecalciferol supplementation is a safe way to increase 25 (OH)D concentrations in kidney transplant recipients, but the small number of treated patients included in these studies and their short follow-up do not allow any conclusion on the effect of these treatments on kidney function. [61][62][63] Our results should encourage randomized controlled trials evaluating the effect of early cholecalciferol supplementation on renal allograft function and provide valuable information on the magnitude of the expected effects of such treatments on renal function and histologic features.…”
Section: Discussionmentioning
confidence: 94%
“…VDR has also been reported to regulate a variety of metabolic pathways, such as those involved in kidney diseases, immune responses and cancers. Moreover, recent evidence has demonstrated that VDR has a protective role in cardiac hypertrophy [152] , heart failure after cardiac remodeling [153] and MI/R injury [154] . LXRs have two receptor subtypes-LXRα (NR1H3) and LXRβ (NR1H2)-that exhibit different expression patterns and perform different functions [155] .…”
Section: Endoplasmic Reticulum Stress Is Involved In the Development mentioning
confidence: 99%
“…Several studies have shown that cardiac myocytes express a functional VDR, which is primarily located in the nucleus and within, or adjacent to the t-tubules [5][6][7][8][9][10][11]. Cardiac fibroblasts also express the VDR.…”
Section: Myocardial Vdr Expression and Metabolismmentioning
confidence: 99%
“…Cardiac fibroblasts also express the VDR. Importantly, myocardial hypertrophy is associated with an increased expression of the VDR in cardiac myocytes as well as in cardiac fibroblasts [11]. Furthermore, it has been shown that cardiac myocytes and fibroblasts express the enzymes 1a-hydroxylase and 24-hydroxylase [11,12].…”
Section: Myocardial Vdr Expression and Metabolismmentioning
confidence: 99%
See 1 more Smart Citation